Pembelajaran Digital ( Digital Learning ) Bagi Guru SD di Desa Bontoala, Kabupaten Gowa Sulawesi Selatan - Iin Almeina Loebis; Fahrisal Husain; Sri Maya; Fitriani Kadir; Kasmawati Kasmawati (Smart Education, 2022)
Abstract:. During the pandemic, almost all levels of education felt the negative impact of the spread of covid, especially elementary school students. Teachers and teaching staff are faced with a difficult time, due to changes in the way of teaching in the classroom. Under normal circumstances, the teacher teaches in class and gives material to his students. With the pandemic period that we are facing now, teachers are no longer in class, but are learning online from home, and material must still be delivered to students or their students. The teacher must already know the method of teaching besides delivering material in front of the class. With the condition that the teacher must continue to deliver material even when he is not in class to meet face to face with his students, the teacher must use another learning method, namely by using digital learning. The development of digital technology has provided technology as a digital medium with benefits in an effort to motivate elementary school students to study during a pandemic. Utilizing digital media in learning is very important to help the online learning process during a pandemic. This media plays a very important role as a medium for information transfer and distance learning interactions. By using digital learning, a teacher not only conducts questions and answers, discussions, group work, role plays in class, but students are also invited to learn using other learning media, such as Youtube and E-learning. Keywords: teacher; student; learningAbstrak: Pada masa pandemic, hampir di semua jenjang pendidikan merasakan dampak yang buruk dengan adanya penyebaran covid, khususnya murid Sekolah Dasar. Guru dan staff pengajar di hadapkan pada masa yang sulit, karena berubahnya cara mengajar di kelas. Pada keadaan normal, guru mengajar di kelas dan memberikan materi kepada siswanya. Dengan masa pandemic yang kita hadapi sekarang, guru tidak lagi masuk kelas, melainkan belajar daring dari rumah, dan materi harus tetap disampaikan kepada peserta didik atau siswanya. Guru harus sudah mengetahui metode cara mengajar selain menyampaikan materi di depan kelas. Dengan keadaan guru harus tetap menyampaikan materi walau dalam keadaan tidak masuk kelas bertemu langsung dengan peserta didiknya, guru harus menggunakan metode pembelajaran yang lain, yaitu dengan menggunakan pembelajaran digital. Perkembangan teknologi digital telah memberikan Teknologi sebagai media digital memiliki manfaat dalam upaya memotivasi belajar siswa Sekolah Dasar selama pandemi. Memanfaatkan media digital dalam pembelajaran sangat penting untuk membantu proses pembelajaran daring selama pandemi. Media ini sangat berperan sebagai media transfer informasi dan interaksi pembelajaran jarak jauh. Dengan menggunakan pembelajaran digital seorang guru tidak hanya melakukan tanya jawab, berdiskusi, kerja kelompok, bermain peran di dalam kelasnya, tetapi siswa juga diajak untuk belajar dengan menggunakan media belajar yang lain, seperti Youtube dan E- learning. Kata kunci: guru; siswa; belajar